Should we calculate arterial stiffness gradient in middle-aged women with increased cardiovascular risk?. (4th May 2019) - Laucyte-Cibulskiene, Agne; Vickiene, Alvita; Ryliskyte, Ligita; Badariene, Jolita; Rimsevicius, Laurynas; Miglinas, Marius
Abstract: Purpose: The study was designed to evaluate clinical and laboratory determinants pulse wave velocity (PWV) ratio in women at the age of 50–65 years without overt cardiovascular disease but having elevated cardiovascular risk, such as hypertension, obesity, diabetes and hypercholesterolemia. Materials and methods: We analyzed data from 1170 women enrolled in the national-wide primary prevention program. Univariate and multivariate linear regression analysis was used to establish independent risk factors in groups based on clinical data, laboratory values, and comorbidities. Arterial stiffness was evaluated using applanation tonometry technique (SphygmoCor). The PWV ratio was calculated by dividing cfPWV to crPWV. Results: In multivariate logistic regression analysis, age (OR = 1.109, p < .001), waist circumference (OR = 1.021, p = .001) and mean arterial pressure (OR = 1.031, p < .001) were found as independent clinical determinants of PWV ratio, while independent laboratory determinants were urine albumin to creatinine ratio (OR = 1.189, p = .010), triglycerides (OR = 1.161, p = .034), glucose (OR = 1.28, p = .001) and eGFR (OR = 0.998, p = .007). Diabetes (OR = 1.811, p = .029), hypertension (OR = 2.784, p = .042) and menopause (OR = 1.054, p = .018) were established as independent factors in comorbidities group. The analysis confirmed that PWV ratio (R 2 = 0.0667, p < .001), as well as carotid radial (R 2 = 0.0341, p < .001) and carotid femoral PWV (R 2 = 0.1752, p < .001) is affected by mean arterial blood pressure. Conclusions: Age, abdominal obesity, blood pressure, triglycerides, glucose, kidney function parameters and menopause all are associated with PWV ratio. More importance to women with high cardiovascular risk should be given whilst screening and stratifying further progression of the disease.